2017
DOI: 10.1365/s40896-017-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Perspectives on Goals in Coaching Practice. An Integrated Model of Goal-focused Coaching

Abstract: Schlüsselwörter Zieltheorie · Zielfindung · Zielformulierung · Zielumsetzung Integrating Perspectives on Goals in Coaching Practice. An Integrated Model of Goal-focused Coaching AbstractThis article describes well-known theories on goal alignment, goal articulation and goal implementation. Based on the described elements, an integrative model of goal-oriented coaching is developed. The model can support coaches to help their clients in aligning and implementing goals. Goals are thereby not considered as monoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…Loebbert sieht eine "bedeutende Innovation von Coaching" (2016, S. 7-8) darin, Beratung von den Resultaten her zu denken und auf die individuelle Leistung zu fokussieren (vgl. auch Greif und Benning-Rohnke 2015;Wastian und Poetschki 2016;Grant 2018). Die Optimierung der Wirksamkeit ist für ihn das zentrale Beratungsziel, und er sieht in "Selbstwirksamkeitserleben, Selbstaktualisierung und Selbststeuerung die wichtigsten Faktoren für erfolgreiches Handeln" (ib.…”
Section: Was Ist Coaching?unclassified
“…Loebbert sieht eine "bedeutende Innovation von Coaching" (2016, S. 7-8) darin, Beratung von den Resultaten her zu denken und auf die individuelle Leistung zu fokussieren (vgl. auch Greif und Benning-Rohnke 2015;Wastian und Poetschki 2016;Grant 2018). Die Optimierung der Wirksamkeit ist für ihn das zentrale Beratungsziel, und er sieht in "Selbstwirksamkeitserleben, Selbstaktualisierung und Selbststeuerung die wichtigsten Faktoren für erfolgreiches Handeln" (ib.…”
Section: Was Ist Coaching?unclassified
“…Goals are seen as a This paper is available online at www.ijarbm.org multi-faceted element in the coaching process. Grant (2017) developed an integrative model for goal work in coaching, for example. Success here lies in the coach's informed, flexible handling of the model (Grant, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Grant (2017) developed an integrative model for goal work in coaching, for example. Success here lies in the coach's informed, flexible handling of the model (Grant, 2017). In the qualitative survey by Wastian & Poetschki (2016), it was found that working with goals dominates the entire coaching process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations